Microbial micritic cementation in deep time: Implications for early marine lithification and paleoenvironmental reconstruction - Belkhedim, Salim; Eberli, Gregor P.; López Correa, Matthias; Sadji, Radouane; Nemra, Abdelkrim; Benhamou, Miloud; Munnecke, Axel (Sedimentary Geology, 2024)
Early micritic cementation is important to reconstruct paleoenvironments of sedimentary gaps. However, due to their scarcity in ancient records, their initial mineralogy (low-magnesium calcite (LMC), high-magnesium calcite (HMC), aragonite), as well as their origin (biotic or abiotic) and paleoenvironments are still controversial. Herein, based on fluorescence microscopy (FL), cathodoluminescence microscopy (CL), and microdrilling carbon and oxygen isotope analyses, we investigate well developed micritic cements in lower Pliensbachian limestones from the Traras Mountains, northwestern Algeria. Evidence for a microbiological influence in the formation of these cements is given by their irregular morphology, the presence of clotted micropeloidal structures, as well as their bright fluorescence under FL. Together, they reflect precipitation of the micritic cements under microbial control via active and/or passive mechanisms, in the presence of organic matter. Their orange luminescence and low δ18O signals suggest their initial precipitation by sea-water as HMC before being recrystallized into LMC within the meteoric and/or burial realm. These micritic cements, including anisopachous and meniscus-like cements are thought to be precipitated within the marine phreatic zone, as they are associated mainly with isopachous fibrous cements, which is in contrast to their widespread attribution as typical and indicative fabrics of the marine vadose zone. In addition, it has been shown that crystalline cements are developed always upon the early micritic envelopes and micritic cements. These observations which are in line with recent studies conducted on modern deposits confirm that preservation of marine microbial cements in deep time is crucial not only for early grain stabilization, but also serving as a foundation for the subsequent crystal growth.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Crystal growth; Early micritic cementation; Grain stabilization; Initial mineralogy; Marine phreatic; Microbial control; Organic matter